(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
The aim of the paper is to determine how much intangible motives are involved in nursing satisfaction. The research population consisted of nurses with secondary and university degrees in the field of multiple health centers in the central part of Croatia. Random selection based on data collected from different nursing associations was used. The survey was conducted in 2019. The dependent variable is the nurses’ satisfaction. There are five independent variables: position in the organization, independence in work, communication, work organization and working hours, education and career development. Among the variables included, the most significant correlation with nurses’ satisfaction was their existing position in the organization of the health care institution, which is followed by education and career development. Communication is the lowest-ranked intangible motive correlated with respondent satisfaction. The lessons learned are believed to have value and carry an initial message. The intangible motives for creating nursing satisfaction identified in this research can realistically be an incentive and a roadmap for public health managers in a context where the transition economy is unable to respond to the pace of growth in health needs and health spending through an existing approach where material motivations have dominated in creating satisfaction for healthcare professionals. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.